The Internet of Robotic Things: A review of concept, added value and applications. (23rd February 2018) - Simoens, Pieter; Dragone, Mauro; Saffiotti, Alessandro
The Internet of Robotic Things is an emerging vision that brings together pervasive sensors and objects with robotic and autonomous systems. This survey examines how the merger of robotic and Internet of Things technologies will advance the abilities of both the current Internet of Things and the current robotic systems, thus enabling the creation of new, potentially disruptive services. We discuss some of the new technological challenges created by this merger and conclude that a truly holistic view is needed but currently lacking.